The Crisis of Moral Degradation among Adolescents: Technology Based Islamic Education Learning as an Educational Solution - Dertha Mukhtar; Supratman Supratman; Ade Putra Hayat; Rifka Haida Rahma; Ramadhoni Aulia Gusli (The Future of Education Journal, 2026)
The phenomenon of moral degradation among adolescents in the digital era has become increasingly alarming due to the influence of social media, weak self-control, and limited digital religious literacy. This study aims to analyze the urgency of technology-based Islamic Education (PAI) learning innovation as an educational solution to address the moral decline among adolescents. The study employed a qualitative approach using a library research method. Data were obtained from SINTA-accredited national journal articles and reputable international journals published between 2019 and 2025. Data were collected through document analysis and digital literature searches using Google Scholar, the Directory of Open Access Journals (DOAJ), and national and international journal databases. The data were analyzed using content analysis, including data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that technology-based Islamic Education learning innovations, such as digital learning, gamification, microlearning, interactive videos, and social media-based learning platforms, enhance student engagement, strengthen religious character, and improve learners' moral literacy. Furthermore, the integration of technology into Islamic Education serves as an effective medium for internalizing moral values in ways that are more contextual and responsive to the characteristics of the digital generation. Therefore, technology-based Islamic Education learning represents a strategic solution for addressing the growing crisis of moral degradation among adolescents in the Society 5.0 era.